2021
DOI: 10.5534/wjmh.180108
|View full text |Cite
|
Sign up to set email alerts
|

Protein Fingerprinting of Seminal Plasma Reveals Dysregulation of Exosome-Associated Proteins in Infertile Men with Unilateral Varicocele

Abstract: Purpose Aberrant expression of seminal plasma proteins are associated with altered homeostasis that may affect the fertilizing ability of spermatozoa. However, the precise roles of seminal exosomes on sperm function remain unclear. The objective of this study was to identify the differentially expressed proteins (DEPs) associated with varicocele-mediated infertility by comparing seminal plasma protein profile of unilateral varicocele patients with proven fertile donors. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 54 publications
1
16
0
1
Order By: Relevance
“…Oxidative stress is a well-known mechanism for testicular dysfunction in VC-induced infertility, which acts by damaging sperm membrane, proteins, and DNA known to be associated with fertility [33,34]. Results of our study showed upregulation of MDA and ROS/RNS levels in VC rats, in consensus with previous findings [7].…”
Section: Discussionsupporting
confidence: 91%
“…Oxidative stress is a well-known mechanism for testicular dysfunction in VC-induced infertility, which acts by damaging sperm membrane, proteins, and DNA known to be associated with fertility [33,34]. Results of our study showed upregulation of MDA and ROS/RNS levels in VC rats, in consensus with previous findings [7].…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, CDC42 and SEMG2 can be useful candidate biomarkers for primary infertility and APP for secondary infertility. A dysregulated expression of semenogelins has also been reported in SP of men with abnormal semen parameters [ 111 , 117 ] and varicocele [ 120 , 126 , 146 ], confirming the importance of these proteins as markers of infertility. Importantly, this study shows that seminal proteins might permit the identification of the main cause associated with primary and secondary infertility [ 114 ].…”
Section: Proteomic Landscape Of Sp: a Potential Indicator Of Spermmentioning
confidence: 84%
“…Of particular interest, there was an overexpression of ANXA2 and CDC42 and an underexpression of SEMG2 in men with primary infertility and an overexpression of ANXA2 and amyloid precursor protein (APP) in secondary infertility. The overexpression of ANXA2 in both primary and secondary infertility, and the results of earlier studies, showing an altered expression of this protein in SP and prostasomes of subfertile or infertile men [ 89 , 146 , 147 ] suggest its potential utility as a biomarker for both primary and secondary infertility. On the other hand, CDC42 and SEMG2 can be useful candidate biomarkers for primary infertility and APP for secondary infertility.…”
Section: Proteomic Landscape Of Sp: a Potential Indicator Of Spermmentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, we have identified the alterations in seminal plasma proteins associated with exosome functions in varicocele patients. Exosome-associated proteins ANXA2 and KIF5B may serve as potential protein biomarkers of exosomal dysfunction and exosome-mediated infertility in varicocele patients [ 74 ].…”
Section: Future Of Proteomicsmentioning
confidence: 99%